Trends in Anemia Prevalence Among Indian Women Using Revised WHO Hemoglobin Cutoffs: Insights From Repeated Cross-Sectional Surveys (1998–2019) - Anuj Kumar Pandey; Diksha Gautam; Benson Thomas M.; Sutapa Bandyopadhyay Neogi (Anemia)
Conclusion: This study highlights a decline in anemia prevalence, particularly in severe cases during pregnancy. Anemia reduction efforts must rely on country-specific data, especially on the Hb distribution against the background of ferritin level, hemoglobinopathies, prevalence of infections, and inflammations in the population.